The Role of Nutrition in COVID-19 Susceptibility and Severity of Disease: A Systematic Review. Issue 7 (19th May 2021) - James, Philip T; Ali, Zakari; Armitage, Andrew E; Bonell, Ana; Cerami, Carla; Drakesmith, Hal; Jobe, Modou; Jones, Kerry S; Liew, Zara; Moore, Sophie E; Morales-Berstein, Fernanda; Nabwera, Helen M; et al.
ABSTRACT: Background: Many nutrients have powerful immunomodulatory actions with the potential to alter susceptibility to coronavirus disease 2019 (COVID-19) infection, progression to symptoms, likelihood of severe disease, and survival. Objective: The aim was to review the latest evidence on how malnutrition across all its forms (under- and overnutrition and micronutrient status) may influence both susceptibility to, and progression of, COVID-19. Methods: We synthesized information on 13 nutrition-related components and their potential interactions with COVID-19: overweight, obesity, and diabetes; protein-energy malnutrition; anemia; vitamins A, C, D, and E; PUFAs; iron; selenium; zinc; antioxidants; and nutritional support. For each section we provide: 1 ) a landscape review of pertinent material; 2 ) a systematic search of the literature in PubMed and EMBASE databases, including a wide range of preprint servers; and 3 ) a screen of 6 clinical trial registries. All original research was considered, without restriction to study design, and included if it covered: 1 ) severe acute respiratory syndrome coronavirus (CoV) 2 (SARS-CoV-2), Middle East respiratory syndrome CoV (MERS-CoV), or SARS-CoV viruses and 2 ) disease susceptibility or 3 ) disease progression, and 4 ) the nutritional component of interest. Searches took place between 16 May and 11 August 2020. Results: Across the 13 searches, 2732 articles from PubMed and EMBASE, 4164 articles from the preprint servers, and 433 trials were returned. In the final narrative synthesis, we include 22 published articles, 38 preprint articles, and 79 trials. Conclusions: Currently there is limited evidence that high-dose supplements of micronutrients will either prevent severe disease or speed up recovery. However, results of clinical trials are eagerly awaited. Given the known impacts of all forms of malnutrition on the immune system, public health strategies to reduce micronutrient deficiencies and undernutrition remain of critical importance. Furthermore, there is strong evidence that prevention of obesity and type 2 diabetes will reduce the risk of serious COVID-19 outcomes. This review is registered at PROSPERO as CRD42020186194.